Shaping the future of African American film : color-coded economics and the story behind the numbers - Ndounou, Monica White, 1976- (Rutgers University Press, 2013)
Through analysis of the production, funding, and content of thousands of films featuring African Americans in leading and supporting roles, Monica White Ndounou reveals the process of history and film development where race-based economics and the politics of distribution hamstring the making, the expression, and the creative freedom of films about, by, or for people of color.